The European Court of Justice Recognition of Cross-border Welfare Rights through the Reshaping of Member States' Welfare Policies: A Comment on Lena Boucon - Lanceiro,Rui Tavares (2014)
This paper is the written version of the comment presented during the Lisbon International Conference on Social Rights, regarding the paper “The European Court of Justice Recognition of Cross-border Welfare Rights through the Reshaping of Member States' Welfare Policies”, submitted by Lena Boucon. The present paper begins by highlighting its main aspects, and its important contribution for the study of the ECJ's case-law in the field of non-national EU citizens' access to national social policies. However, some critical comments can be made in terms of terminology and methodology. The paper can also be criticized for presenting an incomplete analysis and leaving significant questions unanswered.